Library Service Policy for Universitas Terbuka Distance Education Concept - Mohamad Pandu Ristiyono (Yayasan Putra Adi Dharma, 2024)
Universitas terbuka Library has an important role in supporting the success of distance learning for students. In accordance with regulations on service policies, namely Law no.43 of 2007 concerning libraries, Law no. 14 of 2008 concerning public information and Universitas terbuka rector regulation no. 1151 of 2022 concerning the organisation and governance of the Open University, however, effective and efficient implementation of library service policies is still a challenge. This paper examines the Universitas terbuka library service policy with a focus on aspects of access, collections, and services. Policy analysis is conducted through literature review and interviews with relevant stakeholders. The results of the analysis show that the library access policy must be updated to consider the development of information and communication technology. In addition, increasing library collections in the form of digital learning resources also needs to be the main focus. library service policies must also accommodate student needs by expanding online and mobile services. Universitas terbuka library service policy update is expected to improve the quality of library services for students, thus supporting the achievement of quality distance learning objectives